THE EFFECT OF INFLATION ON ECONOMIC STABILITY IN ISLAMIC PERSPECTIVE - Ismul Fakhri Lubis; Herry Syahbannuddin (Az-Zahra Media Society, 2025)
This paper explores the issue of inflation, its causes and impacts, particularly on economic stability from an Islamic perspective. The author highlights the significant burdens arising from rising prices of basic goods and services, which are often attributed to inflation, as well as its effects that encourage protests against government plans that may worsen the situation. The paper reviews the definition and recognition of inflation in economic discourse, highlights its historical significance, and its negative consequences on purchasing power and public welfare. The author emphasizes the importance of controlling inflation to maintain economic stability, recognizing the government's challenge in striking a balance, as inflation rates that are too low or high can be detrimental. The text also presents insights from Islamic economists, such as Monzer Kahf, who oppose the fallacy of blaming interest rates for inflation, and claim that inflation is related to a surplus of means of payment or a shortage of general supply. The paper concludes by outlining the impact of inflation on economic stability from an Islamic perspective and details strategies to control inflation, involving government policies and individual practices.